Inhibition of microRNA-30a alleviates vascular remodeling in pulmonary arterial hypertension - Wenrui Ma; Zhihua Qiu; Zeyang Bai; Yong Dai; Chang Li; Xiao Chen; Xiaoxiao Song; Dingyang Shi; Yanzhao Zhou; Yajie Pan; Yuhua Liao; Mengyang Liao; et al. (Elsevier, 2021)
The excessive and ectopic pulmonary artery smooth muscle cells (PASMCs) are crucial to the pathogenesis of pulmonary arteriole (PA) remodeling in pulmonary arterial hypertension (PAH). We previously found that microRNA (miR)-30a was significantly increased in acute myocardial infarction (AMI) patients and animals, as well as in cultured cardiomyocytes after hypoxia, suggesting that it might be strongly associated with hypoxia-related diseases. Here, we investigated the role of miR-30a in the PASMC remodeling of PAH. The expression of miR-30a was higher in the serum of PAH patients compared with healthy controls. miR-30a was mainly expressed in PAs and was increased in PASMCs after hypoxia, mediating the downregulation of p53 tumor suppressor protein (P53). Genetic knockout of miR-30a effectively decreased right ventricular (RV) systolic pressure (RVSP), PA, and RV remodeling in the Su5416/hypoxia-induced and monocrotaline (MCT)-induced PAH animals. Additionally, pharmacological inhibition of miR-30a via intratracheal liquid instillation (IT-L) delivery strategy showed high efficiency, which downregulated miR-30a to mitigate disease phenotype in the Su5416/hypoxia-induced PAH animals, and these beneficial effects could be partially reduced by simultaneous P53 inhibition. We demonstrate that inhibition of miR-30a could ameliorate experimental PAH through the miR-30a/P53 signaling pathway, and the IT-L delivery strategy shows good therapeutic outcomes, providing a novel and promising approach for the treatment of PAH.